Preparation of CuCo-Cu@CoCH composite nanoarrays and their application in electrochemical detection of hydrogen peroxide
By preparing the stamen-shaped CuCo-Cu@CoCH composite nanoarray, the problems of small specific surface area of alloys and easy agglomeration of nanoparticles in non-enzymatic hydrogen peroxide detection are solved, and hydrogen peroxide detection performance with high sensitivity and low detection limits are achieved.
Patent Information
- Application Number
- CN202110498095.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-08-11
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2041-08-11
AI Technical Summary
In the prior art, in non-enzymatic hydrogen peroxide detection, the detection performance is poor due to the small specific surface area of the alloy and the nanoparticles of the alloy are prone to agglomeration.
The stamen-shaped CuCo-Cu@CoCH composite nanoarray was prepared by hydrothermal method, and the CuCo alloy and CoCH nanowires were formed using a co-reduction process to improve the conductivity and specific surface area of the material.
An electrode material with excellent performance in hydrogen peroxide detection is achieved, with a linear detection range of 1μM-2000μM, a sensitivity of up to 3570μA mmol L-1cm-2, and a detection limit of 0.97μmol L-1.
Smart Images

Figure CN115704798B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of nanomaterials and electrochemical detection, and in particular to the preparation of a CuCo-Cu@CoCH composite nanoarray and its application in electrochemical detection of hydrogen peroxide. Background Art
[0002] Sensitive and accurate detection of hydrogen peroxide has attracted much attention. Currently, the main detection methods are chemiluminescence, fluorescence spectroscopy, and electrochemical methods. Among them, electrochemical methods are widely used due to their high sensitivity, low detection limit, and low cost. Sensors for detecting hydrogen peroxide using electrochemical methods are mainly divided into enzyme-based sensors and non-enzyme sensors. Non-enzyme electrochemical technology has the advantages of good selectivity, high sensitivity, strong anti-interference ability, low detection limit, and miniaturization, and has been widely studied.
[0003] In non-enzymatic hydrogen peroxide detection, transition metal materials are a common active electrode, especially transition metal alloys, which have good reducibility to hydrogen peroxide and are often used for hydrogen peroxide detection under negative pressure. However, common transition metal alloys have a small specific surface area, and the alloy nanoparticles face the problem of easy agglomeration. Therefore, it is very important to prepare alloy structures with large specific surface area in hydrogen peroxide detection. Summary of the invention
[0004] In order to make up for the shortcomings of the prior art and solve the problem in the prior art of non-enzymatic hydrogen peroxide detection that the alloy has a small specific surface area and the alloy nanoparticles are easy to agglomerate, the present invention provides a preparation method of a CuCo-Cu@CoCH composite nanoarray and its application in electrochemical detection of hydrogen peroxide.
[0005] The present invention uses the common hydroxide nanoarray structure and combines it with the co-reduction process to prepare a stamen-shaped CuCo-Cu@CoCH composite nanoarray, in which the "core" part is CoCH nanowire wrapped with Cu, and the "core head" part is CuCo alloy; compared with the traditional powder catalyst, the electrode prepared by the composite nanomaterial has the advantages of stable structure, good conductivity and large specific surface area. The presence of CuCo particles in the composite nanoarray greatly improves the conductivity of the composite material and has a strong reducing effect on hydrogen peroxide; the large specific surface area is conducive to the adsorption of the detection substance; it shows excellent performance in hydrogen peroxide detection, with a linear detection range of 1μM-2000μM and a sensitivity of 1μmol L -1 -100 μmol L -1 Up to 3570μAmmol L -1 cm -2 , at 100 μmol L -1 -2000 μmol L -1The sensitivity is up to 3290μA mmol L -1 cm -2 The detection limit was 0.97 μmol L -1 .
[0006] The technical solution of the present invention is:
[0007] A method for preparing a CuCo-Cu@CoCH composite nanoarray comprises the following steps:
[0008] 1) Preparation of basic cobalt carbonate nanoarrays on nickel foam substrate by hydrothermal method;
[0009] 2) immersing the basic cobalt carbonate nanoarray obtained in step 1) in a copper ion solution with a molar concentration of 0.05 to 1 mol / L, reacting at a certain temperature for a period of time, washing, and drying;
[0010] 3) immersing the nanoarray treated in step 2) in a reducing solution with a molar concentration of 0.01 to 0.1 mol / L, and reacting at a certain temperature for a certain time;
[0011] 4) The sample treated in step 3) is taken out, washed and dried to obtain a CuCo-Cu@CoCH composite nanoarray. In step 1) of the present invention, basic cobalt carbonate (chemical formula: Co(CO3)) is prepared on nickel foam by a hydrothermal method. 0.5 (OH, abbreviated as CoCH) nanoarrays, and then the basic cobalt carbonate nanoarrays are immersed in a copper ion solution to cause a replacement reaction, where part of the cobalt is replaced by copper; the treated sample is then placed in a reducing solution, where the reducing substance can reduce H + The subsequent metal (Cu 2+ , Ag + etc.), Co 2+ Located in H + Previously, it was difficult to be reduced by sodium borohydride. After doping with Cu ions, a CuCo alloy can be obtained by co-reduction. In addition, the present invention has a high requirement for the concentration of the copper ion solution. If the copper ion concentration is too high, the basic cobalt carbonate nanoarray will be destroyed due to the acidity of the copper ion solution, causing the basic cobalt carbonate nanowires to peel off on the nickel foam; if the copper ion concentration is too low, it will make it difficult for the ion exchange reaction to proceed in the direction of producing copper hydroxide precipitation. As a preferred embodiment, the specific steps of step 1) preparing the basic cobalt carbonate (CoCH) nanoarray include:
[0012] a) cleaning and drying the nickel foam sheet to obtain a clean nickel foam electrode;
[0013] b) dissolving urea, cobalt acetate tetrahydrate and ammonium fluoride in deionized water to obtain solution A;
[0014] c) pouring solution A into the polytetrafluoroethylene liner of the reaction kettle, then placing the cleaned nickel foam in step a) therein, and tightening the reaction kettle;
[0015] d) placing the reaction kettle in step c) in an oven and keeping it warm for a certain period of time;
[0016] e) After the oven is cooled down, the reactor is taken out, and the electrodes are taken out from the inner lining of the reactor, and are washed with deionized water and an organic solvent respectively, and then dried in an oven to generate basic cobalt carbonate nanoarrays on the nickel foam substrate.
[0017] As a preferred embodiment, in step 2), the copper salt used to prepare the copper ion solution is one or more of copper chloride, copper sulfate, copper nitrate, and copper acetate.
[0018] As a preferred embodiment, the reaction temperature in step 2) is 20-80°C and the reaction time is 30-70 min. The degree of ion exchange of the reaction is changed by adjusting the soaking time. Too short a soaking time results in less CuCo alloy generated in the next step, which leads to a decrease in the ability to detect hydrogen peroxide and a smaller detection concentration range. Too long a replacement time will greatly change the morphology of CuCo-Cu@CoCH, and even the peeling of the CoCH nanoarray and the CuCo alloy on the nickel foam, resulting in a decrease in the ability to detect hydrogen peroxide and a smaller detection concentration range.
[0019] As a preferred embodiment, in step 3), the reducing solution is an aqueous solution of sodium borohydride, ascorbic acid or hydrazine hydrate.
[0020] As a preferred embodiment, in step 3), the reaction temperature is 20-80° C. and the reaction time is 5-60 min.
[0021] As a preferred embodiment, in step 4), the drying temperature is 50 to 80° C. and the drying time is 8 to 24 hours.
[0022] As a preferred embodiment, in step 2), the concentration of the copper ion solution is 0.1-0.5 mol / L.
[0023] As a preferred embodiment, in step 3), the concentration of the reducing solution is 0.03 to 0.07 mol / L
[0024] The CuCo-Cu@CoCH composite nanoarray prepared by the method is used as a hydrogen peroxide electrochemical sensor. The beneficial effects of the present invention are:
[0025] 1. A composite nanomaterial of metal particles and metal compounds is obtained by a simple and easy-to-operate method. CoCH cannot be reduced by aqueous solutions of reducing agents such as sodium borohydride, hydrazine hydrate, and ascorbic acid, but Cu(OH)2 can be reduced by these agents. 2+After partial replacement of CoCH, Co 2+ Can be with Cu 2+ Co-reduction is carried out to obtain CuCo alloy particles.
[0026] The presence of CuCo particles in the CuCo-Cu@CoCH composite nanoarray greatly improves the conductivity of the composite material and has a strong reducing effect on hydrogen peroxide; at the same time, the one-dimensional nanoarray structure of CoCH has a large specific surface area, which is conducive to the adsorption of the detection substance; therefore, the CuCo-Cu@CoCH composite nanoarray prepared by the present invention exhibits excellent performance in hydrogen peroxide detection.
[0027] 2. The prepared composite nanomaterials are used for electrochemical detection of hydrogen peroxide; the linear range of the sensor is 1 μmol L -1 ~2000 μmol L -1 , with a sensitivity of 1 μmol L -1 ~100 μmol L -1 Up to 3570μA mmol L -1 cm -2 , at 100 μmol L -1 ~2000 μmol L -1 The sensitivity is up to 3290μA mmol L -1 cm -2 The detection limit was 0.97 μmol L -1 (LOD = 3σ / N, LOD limit of detection, σ standard deviation of background current, N sensitivity). BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0029] Figure 1 XRD pattern of the CuCo-Cu@CoCH composite nanoarray (including nickel foam matrix) prepared by the present invention;
[0030] Figure 2 XRD pattern of CuCo-Cu@CoCH composite nanoarrays scraped from nickel foam substrate;
[0031] Figure 3 This is a scanning electron microscope image of the CuCo-Cu@CoCH composite nanoarray prepared in the present invention;
[0032] Figure 4 Transmission electron microscopy image and element diffraction analysis of the CuCo-Cu@CoCH composite nanoarray prepared in the present invention;
[0033] Figure 5a The electrochemical performance diagram of CuCo-Cu@CoCH composite nanoarray; The CV curves of three different samples, the solution contains 800 μmol L -1 Hydrogen peroxide in phosphate buffer (0.1 mol L -1 pH = 7), scanning voltage -0.7 V to 0 V, scanning rate 100 mV s -1 ;
[0034] Figure 5b The electrochemical performance diagram of CuCo-Cu@CoCH composite nanoarray; The IT curve at a voltage of -0.25V (vs.SCE), three different samples were dripped with a certain concentration of hydrogen peroxide at intervals, and the relationship between the concentration of hydrogen peroxide and the current density was recorded;
[0035] Figure 6 This is the IT curve of the CuCo-Cu@CoCH composite nanoarray at a voltage of -0.25V. The inset is a local enlarged view of the IT curve.
[0036] Figure 7 The relationship between the current response and hydrogen peroxide concentration of CuCo-Cu@CoCH composite nanoarray at a voltage of -0.25V;
[0037] a is the hydrogen peroxide concentration of 1 to 2000 μmol L -1 The relationship between the current response and the hydrogen peroxide concentration when b is 1 to 100 μmol L -1 The relationship between the current response and the hydrogen peroxide concentration when
[0038] Figure 8 This is a scanning electron microscope image of the CuCo-Cu@CoCH composite nanoarray prepared in Comparative Example 1;
[0039] Fig. 9 This is a scanning electron microscope image of the CuCo-Cu@CoCH composite nanoarray prepared in Comparative Example 2. DETAILED DESCRIPTION
[0040] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. The described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] Reagents and specifications used in the examples:
[0042] Cobalt acetate tetrahydrate: Analytical grade from Sinopharm Chemical Reagent Co., Ltd.
[0043] Copper chloride dihydrate: Analytical grade from Sinopharm Chemical Reagent Co., Ltd.
[0044] Copper sulfate pentahydrate: analytical grade from Sinopharm Chemical Reagent Co., Ltd.
[0045] Copper nitrate trihydrate: Analytical grade from Sinopharm Chemical Reagent Co., Ltd.
[0046] Urea: analytical grade from Tianjin Fengchuan Chemical Reagent Technology Co., Ltd.
[0047] Ammonium fluoride: analytical grade from Tianjin Kemeiou Chemical Reagent Co., Ltd.
[0048] Sodium borohydride: analytical grade from Sinopharm Chemical Reagent Co., Ltd.
[0049] Hydrazine hydrate: analytical grade from Tianjin Damao Chemical Reagent Factory
[0050] Anhydrous ethanol: analytical grade from Sinopharm Chemical Reagent Co., Ltd.
[0051] 95% ethanol: analytical grade from Sinopharm Chemical Reagent Co., Ltd.
[0052] 1. Preparation Example
[0053] Example 1
[0054] Preparation of CuCo-Cu@CoCH composite nanoarrays, including the following steps:
[0055] 1) Take nickel foam cut into 4.0 cm long, 1.0 cm wide and 0.1 cm thick, and add 3 mol L -1 The samples were ultrasonically cleaned in hydrochloric acid, deionized water and anhydrous ethanol for 15 min, and then dried in an oven at 60 °C overnight;
[0056] 2) Dissolve 0.249 g of cobalt acetate tetrahydrate, 0.30 g of urea and 0.074 g of ammonium fluoride in 20 ml of deionized water to obtain solution A;
[0057] 3) Pour solution A into a 50ml polytetrafluoroethylene liner, then place the cut nickel foam into the liner at an angle, place the liner in the reactor, tighten it, place it in a 120℃ oven, and keep it warm for 8h;
[0058] 4) After the reactor is cooled, open the reactor, take out the nickel foam, wash it with deionized water and 95% ethanol respectively, and dry it in a 60°C oven for 5 hours to obtain sample A;
[0059] 5) Weigh 0.85 g of cupric chloride dihydrate and dissolve it in 50 mL of deionized water to obtain solution B;
[0060] 6) Place solution B in a 60°C water bath, and place the nickel foam in solution B; take out the sample after 1 hour, wash it with deionized water, and dry it in an oven to obtain sample B;
[0061] 7) Weigh 0.075 g of sodium borohydride and dissolve it in 40 mL of deionized water to obtain solution C;
[0062] 8) Immerse sample B in solution C, react at 30°C for 10 min, take out the sample, wash it with deionized water, and dry it in an oven at 70°C for 8 h to obtain sample C.
[0063] Example 2
[0064] Preparation of CuCo-Cu@CoCH composite nanoarrays, including the following steps:
[0065] 1) Take nickel foam cut into 4.0 cm long, 1.0 cm wide and 0.1 cm thick, and add 3 mol L -1 The samples were ultrasonically cleaned in hydrochloric acid, deionized water and anhydrous ethanol for 15 min, and then dried in an oven at 60 °C overnight;
[0066] 2) Dissolve 0.249 g of cobalt acetate tetrahydrate crystal water, 0.30 g of urea and 0.074 g of ammonium fluoride in 20 ml of deionized water to obtain solution A;
[0067] 3) Pour solution A into a 50ml polytetrafluoroethylene liner, then place the cut nickel foam into the liner at an angle, place the liner in the reactor, tighten it, place it in a 120℃ oven, and keep it warm for 8h;
[0068] 4) After the reactor is cooled, open the reactor, take out the nickel foam, wash it with deionized water and 95% ethanol respectively, and dry it in a 60°C oven for 5 hours to obtain sample A;
[0069] 5) Weigh 1.25 g of copper sulfate pentahydrate and dissolve it in 50 mL of deionized water to obtain solution B;
[0070] 6) Place solution B in a 60°C water bath, and place the nickel foam in solution B; take out the sample after 1 hour, wash it with deionized water, and dry it in an oven to obtain sample B;
[0071] 7) Weigh 0.075 g of sodium borohydride and dissolve it in 40 mL of deionized water to obtain solution C;
[0072] 8) Immerse sample B in solution C, react at 50°C for 5 minutes, take out the sample, wash it with deionized water, and dry it in an oven at 60°C for 12 hours to obtain sample C.
[0073] Example 3
[0074] Preparation of CuCo-Cu@CoCH composite nanoarrays, including the following steps:
[0075] 1) Take nickel foam cut into 4.0 cm long, 1.0 cm wide and 0.1 cm thick, and add 3 mol L -1 The samples were ultrasonically cleaned in hydrochloric acid, deionized water and anhydrous ethanol for 15 min, and then dried in an oven at 60 °C overnight;
[0076] 2) Dissolve 0.249 g of cobalt acetate tetrahydrate crystal water, 0.30 g of urea and 0.074 g of ammonium fluoride in 20 ml of deionized water to obtain solution A;
[0077] 3) Pour solution A into a 50ml polytetrafluoroethylene liner, then place the cut nickel foam into the liner at an angle, place the liner in the reactor, tighten it, place it in a 120℃ oven, and keep it warm for 8h;
[0078] 4) After the reactor is cooled, open the reactor, take out the nickel foam, wash it with deionized water and 95% ethanol respectively, and dry it in a 60°C oven for 5 hours to obtain sample A;
[0079] 5) Weigh 0.85 g of cupric chloride dihydrate and dissolve it in 50 mL of deionized water to obtain solution B;
[0080] 6) Place solution B in a 60°C water bath, and place nickel foam in solution B; take out the sample after 1 hour, wash it with deionized water, and dry it in an oven to obtain sample B;
[0081] 7) Take a certain volume of hydrazine hydrate and dilute it to 0.1 mol L -1 , to obtain solution C;
[0082] 8) Immerse sample B in solution C, react at 30°C for 10 min, take out the sample, wash it with deionized water, and dry it in an oven at 60°C for 12 h to obtain sample C;
[0083] Sample C obtained in Example 1 was selected for material characterization. The results are as follows: Figure 1 , Figure 2 , Figure 3 , Figure 4 As shown. Among them,
[0084] Figure 1 This is the XRD pattern of the CuCo-Cu@CoCH composite nanoarray (including the nickel foam matrix) prepared in the present invention; due to the shielding effect of the nickel foam, the peak of CoCH is not obvious.
[0085] Figure 2 is the XRD pattern of CuCo-Cu@CoCH composite nanoarray scraped from nickel foam substrate; Figure 2 It can be seen that the nanomaterial on the substrate is basic cobalt carbonate (chemical formula is Co(CO3) 0.5 (OH), abbreviated as CoCH) nanoarrays.
[0086] Figure 3 This is a scanning electron microscope image of the CuCo-Cu@CoCH composite nanoarray prepared in the present invention; CoCH nanowires grow vertically on the nickel foam substrate, and nanoparticles grow on the top of the nanowires.
[0087] Figure 4 Transmission electron microscopy image and element diffraction analysis of the CuCo-Cu@CoCH composite nanoarray prepared in the present invention; Figure 4 a is the transmission electron image of CuCo-Cu@CoCH, from which it can be seen that there are particles at the top of the nanowires. Figure 4 b and 4d are high-resolution transmission electron images, where 0.265 and 0.268 nm correspond to the lattice spacing of CoCH (221) and (231), respectively, and 0.207 nm corresponds to the lattice spacing of CuCo (111). Figure 4 c-4g is the element mapping diagram of Cu, Co, and O. It can be seen that the diameter of Cu distributed on the nanowire is wider than that of Co and O, indicating that the inside of the nanowire is CoCH, the outer layer is wrapped with a layer of Cu, and the top is CuCo alloy particles. Figure 3 , Figure 4 It can be seen that the prepared CuCo-Cu@CoCH is stamen-shaped, in which the "stamen" part is CoCH nanowire wrapped with Cu, and the "stamen head" part is CuCo alloy. The nanoarray is a composite structure of CuCo and Cu wrapped with CoCH; this should be because the substituted copper element is mainly distributed on the outside and top of the nanowire.
[0088] Comparative Example 1 Preparation of CuCo-Cu@CoCH composite nanoarrays, comprising the steps of:
[0089] 1) Take nickel foam cut into 4.0 cm long, 1.0 cm wide and 0.1 cm thick, and add 3 mol L -1 The samples were ultrasonically cleaned in hydrochloric acid, deionized water and anhydrous ethanol for 15 min, and then dried in an oven at 60 °C overnight;
[0090] 2) Dissolve 0.249 g of cobalt acetate tetrahydrate, 0.30 g of urea and 0.074 g of ammonium fluoride in 20 mL of deionized water to obtain solution A;
[0091] 3) Pour solution A into a 50 mL polytetrafluoroethylene liner, then place the cut nickel foam in the liner at an angle, place the liner in the reactor, tighten it, and place it in a 120°C oven for 8 hours;
[0092] 4) After the reactor is cooled, open the reactor, take out the nickel foam, wash it with deionized water and 95% ethanol respectively, and dry it in a 60°C oven for 5 hours to obtain sample A;
[0093] 5) Weigh 0.85 g of cupric chloride dihydrate and dissolve it in 50 mL of deionized water to obtain solution B;
[0094] 6) Place solution B in a 60°C water bath, and place the nickel foam in solution B; take out the sample after 10 minutes, wash it with deionized water, and dry it in an oven to obtain sample B;
[0095] 7) Weigh 0.075 g of sodium borohydride and dissolve it in 40 mL of deionized water to obtain solution C;
[0096] 8) Immerse sample B in solution C, react at 30°C for 10 min, take out the sample, wash it with deionized water, and dry it in an oven at 70°C for 8 h to obtain sample C.
[0097] The scanning electron microscope image of sample C obtained in Comparative Example 1 is as follows Figure 8 shown by Figure 8 It can be seen that the immersion time in the copper ion solution is too short, resulting in very little CuCo alloy being generated.
[0098] Comparative Example 2
[0099] 1) Take nickel foam cut into 4.0 cm long, 1.0 cm wide and 0.1 cm thick, and add 3 mol L -1 The samples were ultrasonically cleaned in hydrochloric acid, deionized water and anhydrous ethanol for 15 min, and then dried in an oven at 60 °C overnight;
[0100] 2) Dissolve 0.249 g of cobalt acetate tetrahydrate, 0.30 g of urea and 0.074 g of ammonium fluoride in 20 mL of deionized water to obtain solution A;
[0101] 3) Pour solution A into a 50 mL polytetrafluoroethylene liner, then place the cut nickel foam in the liner at an angle, place the liner in the reactor, tighten it, and place it in a 120°C oven for 8 hours;
[0102] 4) After the reactor is cooled, open the reactor, take out the nickel foam, wash it with deionized water and 95% ethanol respectively, and dry it in a 60°C oven for 5 hours to obtain sample A;
[0103] 5) Weigh 0.85 g of cupric chloride dihydrate and dissolve it in 50 mL of deionized water to obtain solution B;
[0104] 6) Place solution B in a 60°C water bath, and place nickel foam in solution B; take out the sample after 90 minutes, wash it with deionized water, and dry it in an oven to obtain sample B;
[0105] 7) Weigh 0.075 g of sodium borohydride and dissolve it in 40 mL of deionized water to obtain solution C;
[0106] 8) Immerse sample B in solution C, react at 30°C for 10 min, take out the sample, wash it with deionized water, and dry it in an oven at 70°C for 8 h to obtain sample C.
[0107] The scanning electron microscope image of sample C obtained in Comparative Example 2 is as follows Fig. 9 shown by Fig. 9 It can be seen that the long immersion time in the copper ion solution leads to the peeling of CoCH nanowires and CuCo alloy.
[0108] It can be seen from Example 1, Comparative Example 1 and Comparative Example 2 that the immersion time of CoCH nanowires in the copper ion solution is one of the key conditions for the success of the present invention.
[0109] 2. Application Examples
[0110] Application Example 1
[0111] Ⅰ. A three-electrode system was constructed with the prepared sample C as the working electrode, a graphite rod as the counter electrode, saturated calomel as the reference electrode, and phosphate buffer (PBS pH=7) as the test solution;
[0112] Ⅱ. Test the response of different modified electrodes to hydrogen peroxide. Sample C was used as the working electrode, containing 800 μmol L -1 The phosphate buffer solution of hydrogen peroxide was used as the test solution. The CV curve was tested at a scan rate of 100 mV s -1 , record the obtained data.
[0113] III. Test the response of the modified electrode to different concentrations of hydrogen peroxide. Take sample C as the working electrode, fix the voltage at -0.25V in phosphate buffer, test the IT curve, and when the current no longer changes with time, add a certain concentration of hydrogen peroxide to the solution at regular intervals under stirring, and record the obtained data.
[0114] Application Example 2
[0115] Ⅰ. A three-electrode system was constructed with the prepared sample CoCH as the working electrode, a graphite rod as the counter electrode, saturated calomel as the reference electrode, and phosphate buffer (PBS PH=7) as the test solution;
[0116] Ⅱ. Test the response of different modified electrodes to hydrogen peroxide. Sample C was used as the working electrode, containing 800 μmol L -1 The phosphate buffer solution of hydrogen peroxide was used as the test solution. The CV curve was tested at a scan rate of 100 mV s -1 , record the obtained data.
[0117] III. Test the response of the modified electrode to different concentrations of hydrogen peroxide. Take sample C as the working electrode, fix the voltage at -0.25V in phosphate buffer, test the IT curve, and when the current no longer changes with time, add a certain concentration of hydrogen peroxide to the solution at regular intervals under stirring, and record the obtained data.
[0118] Application Example 3
[0119] Ⅰ. A three-electrode system was constructed with the prepared sample Cu(OH)2@CoCH as the working electrode, a graphite rod as the counter electrode, saturated calomel as the reference electrode, and phosphate buffer (PBS PH=7) as the test solution;
[0120] Ⅱ. Test the response of different modified electrodes to hydrogen peroxide. Sample C was used as the working electrode, containing 800 μmol L -1 The phosphate buffer solution of hydrogen peroxide was used as the test solution. The CV curve was tested at a scan rate of 100 mV s -1 , record the obtained data.
[0121] III. Test the response of the modified electrode to different concentrations of hydrogen peroxide. Take sample C as the working electrode, fix the voltage at -0.25V in phosphate buffer, test the IT curve, and when the current no longer changes with time, add a certain concentration of hydrogen peroxide to the solution at regular intervals under stirring, and record the obtained data.
[0122] The electrochemical performance test results of the electrical sensor are as follows Figure 5a , Figure 5b , Figure 6 , Figure 7 shown.
[0123] Figure 5a The electrochemical performance diagram of CuCo-Cu@CoCH composite nanoarray; The CV curves of three different samples, the solution contains 800 μmol L -1 Hydrogen peroxide in phosphate buffer (0.1 mol L -1 pH = 7), scanning voltage -0.7 V to 0 V, scanning rate 100 mV s -1 ;
[0124] Depend on Figure 5a It can be seen that the three different materials contain 800 μmol L -1 In the case of hydrogen peroxide,
[0125] The current response of CuCo-Cu@CoCH is larger.
[0126] Figure 5b The electrochemical performance diagram of CuCo-Cu@CoCH composite nanoarray; The IT curve at a voltage of -0.25V (vs.SCE), three different samples were dripped with a certain concentration of hydrogen peroxide at intervals, and the relationship between the concentration of hydrogen peroxide and the current density was recorded;
[0127] Depend on Figure 5b It can be seen that the three different materials were dripped with 100μM hydrogen peroxide at regular intervals.
[0128] CoCu-Cu@CoCH exhibits the largest current response.
[0129] Figure 6 This is the IT curve of the CuCo-Cu@CoCH composite nanoarray obtained in Application Example 1 at a voltage of -0.25V, and the inset is a local enlarged view of the IT curve. Figure 6 It reflects the curve of the change of current over time when a certain amount of hydrogen peroxide is added every 60 seconds. As the concentration of hydrogen peroxide increases, the current response appears, and CuCo-Cu@CoCH has good hydrogen peroxide detection performance.
[0130] Figure 7 The relationship between the current response and the hydrogen peroxide concentration of the CuCo-Cu@CoCH composite nanoarray obtained in Example 1 at a voltage of -0.25V;
[0131] Figure 7 a is the concentration of hydrogen peroxide, 1 to 2000 μmol L -1 The relationship between the current response and the hydrogen peroxide concentration when
[0132] Figure 7 It can be seen from a that when the concentration of hydrogen peroxide is 100-2000 μmol L -1 The current is linearly related to the concentration, and the slope is , which represents a sensitivity of 3290 μA mmol L -1 cm -2 .
[0133] Figure 7 b is the concentration of hydrogen peroxide ranging from 1 to 100 μmol L -1 The relationship between the current response and the hydrogen peroxide concentration.
[0134] Figure 7 In b, we can see that the current is linearly related to the concentration of hydrogen peroxide, and the slope represents a sensitivity of 3570 μAmmol L -1 cm -2 .
Claims
1. A method for preparing a CuCo-Cu@CoCH composite nanoarray, characterized in that: The method comprises the following steps: 1) preparing basic cobalt carbonate nanoarrays on a nickel foam substrate by a hydrothermal method; Step 1) The specific steps of preparing the basic cobalt carbonate nanoarray include: a) cleaning and drying the nickel foam sheet to obtain a clean nickel foam electrode; b) dissolving urea, cobalt acetate tetrahydrate and ammonium fluoride in deionized water to obtain solution A; c) pouring solution A into the polytetrafluoroethylene liner of the reaction kettle, then placing the cleaned nickel foam in step a) therein, and tightening the reaction kettle; d) placing the reaction kettle in step c) in an oven at 120° C. for 8 h; e) after the oven is cooled down, the reactor is taken out, the electrodes are taken out from the lining of the reactor, and they are washed with deionized water and an organic solvent respectively, and then dried in an oven to generate a basic cobalt carbonate nanoarray on the nickel foam substrate; 2) immersing the basic cobalt carbonate nanoarray obtained in step 1) in a copper ion solution with a molar concentration of 0.05 to 1 mol / L, reacting at 20 to 80° C. for 30 to 70 min, washing, and drying; 3) immersing the nanoarray treated in step 2) in a reducing solution with a molar concentration of 0.01 to 0.1 mol / L, and reacting at 20 to 80° C. for 5 to 60 minutes; 4) The sample treated in step 3) is taken out, cleaned and dried to obtain a CuCo-Cu@CoCH composite nanoarray.
2. The method for preparing the CuCo-Cu@CoCH composite nanoarray according to claim 1, characterized in that: In step 2), the copper salt used to prepare the copper ion solution is one or more of copper chloride, copper sulfate, copper nitrate and copper acetate.
3. The method for preparing the CuCo-Cu@CoCH composite nanoarray according to claim 1, characterized in that: In step 3), the reducing solution is an aqueous solution of sodium borohydride, ascorbic acid or hydrazine hydrate.
4. The method for preparing the CuCo-Cu@CoCH composite nanoarray according to claim 1 or 3, characterized in that: In step 4), the drying temperature is 50 to 80° C. and the drying time is 8 to 24 hours.
5. The method for preparing the CuCo-Cu@CoCH composite nanoarray according to claim 1, characterized in that: In step 2), the concentration of the copper ion solution is 0.1-0.5 mol / L.
6. The method for preparing the CuCo-Cu@CoCH composite nanoarray according to claim 1, characterized in that: In step 3), the concentration of the reducing solution is 0.03-0.07 mol / L.
7. Use of the CuCo-Cu@CoCH composite nanoarray prepared by the method of claim 1 as a hydrogen peroxide electrochemical sensor.
Citation Information
Patent Citations
Nano porous copper / Cu(OH)2 nanowire array sensor electrode material and preparation method thereof
CN106226382A
Ni(OH)2-Co2(OH)3Cl composite nanometer array electrode materials
CN107887171A